Trk1 potassium transport is crucial for effective Candidozyma auris skin colonization - Adam J. Glawe; Emily F. Eix; Chad J. Johnson; Robert Zarnowski; Maisy K. Andes; James Lazarcik; Katherine A. Henzler-Wildman; Jeniel E. Nett (Proceedings of the National Academy of Sciences, 2026)
The recently emergent fungal pathogen Candidozyma (Candida) auris has produced numerous outbreaks of invasive disease in hospitals worldwide. It is the first fungal pathogen categorized as a global public health threat due to its ability to readily colonize skin, spread efficiently person-to-person, and cause invasive infection with high mortality. Skin colonization not only promotes healthcare spread but also leads to invasive infection via the insertion of medical devices through skin. However, the mechanisms underlying C. auris survival in the skin niche remain poorly understood. Here, we identify potassium (K + ) as a crucial nutrient for efficient growth in this environment. We show that putative high-affinity K + transporter Trk1 is required for C. auris growth on human skin ex vivo. Disruption of TRK1 significantly impairs K + uptake and leads to plasma membrane hyperpolarization, a lower intracellular pH, and sensitivity to cationic stress. These findings demonstrate that TRK1 is necessary for maintaining K + homeostasis during C. auris colonization of human skin, shedding light on pathogenesis for this emerging threat. Given that TRK1 has no known human homologs, the gene product may serve as a promising therapeutic target for development of novel strategies directed at C. auris propagating on skin.